Gestational Diabetes Mellitus and Associated Neonatal Complications in Pakistani Women: A Comparative Study - Uzma Afridi, Arifa Inayat, Asma Hameed, Misbah Munir, Sakina Naeem, Samia Saifullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Gestational diabetes mellitus (GDM) is increasingly prevalent and linked to adverse neonatal outcomes, yet its impact remains under-characterized in many low-resource settings. Objective: To determine the association between GDM and neonatal complications including macrosomia, hypoglycemia, respiratory distress, intensive care admission, and stillbirth at a tertiary care center in Pakistan. Methods: In this Comparative Study conducted from January to December 2022 at Sandeman Provincial Hospital, 70 pregnant women (≥ 28 weeks’ gestation) were enrolled. Thirty-five women diagnosed with GDM by 75 g oral glucose tolerance testing (IADPSG criteria) were matched by age and gestational age to 35 normoglycemic controls. Neonatal outcomes were recorded within 24 hours of birth. Continuous and categorical variables were compared using t tests and chi-square or Fisher’s exact tests, respectively, with p < 0.05 denoting significance. Results: Infants of mothers with GDM exhibited significantly higher rates of macrosomia (28.6 % vs. 8.6 %; p = 0.02) and neonatal hypoglycemia (20.0 % vs. 5.7 %; p = 0.04). Although more GDM-exposed neonates required intensive care (25.7 % vs. 11.4 %; p = 0.09), this did not reach statistical significance. There were no significant differences in respiratory distress (11.4 % vs. 5.7 %; p = 0.68), stillbirth (2.9 % vs. 0 %; p = 0.31), Apgar scores, or length of hospital stay. Conclusions: GDM significantly elevates the risk of macrosomia and early hypoglycemia. These findings underscore the need for universal antenatal screening, stringent glycemic management, and standardized neonatal monitoring protocols to mitigate perinatal morbidity in resource-constrained settings. Keywords: gestational diabetes mellitus; neonatal complications; macrosomia; hypoglycemia; Pakistan; prospective observational study.